1987
DOI: 10.1093/nar/15.10.4049
|View full text |Cite
|
Sign up to set email alerts
|

Single base bulges in small RNA hairpins enhance ethidium binding and promote an allosteric transition

Abstract: A set of four RNA hairpin helices has been prepared by in vitro transcription with T7 RNA polymerase. The hairpins all contain the same nine base pair helix, but with an extra A, C, or U residue forming a bulge at one position; the fourth hairpin is a perfect helix with no bulge. The helix with a bulged A duplicates six base pairs of a helix in the 16S rRNA known to have an unusually high affinity for ethidium bromide [J. M. Kean, S. A. White, and D. E. Draper, Biochemistry 24, 5062 (1985)]. Binding and chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 29 publications
6
51
0
Order By: Relevance
“…Finally, since the geometry of the bulged nucleotide is most probably an important feature of lariat formation, the intra-or extrahelical positioning of the bulged base has to be considered (34,42). The conformation of bulged nucleotides in RNA is not yet known, but by measuring ethidium bromide intercalation near bulged A, C, and U in an RNA helix, it was shown that all three bulged nucleotides have the same pronounced effect on the conformation of the sugar-phosphate backbone (60). Thus, the nucleotide conformations either are identical or differ by only a small free energy.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, since the geometry of the bulged nucleotide is most probably an important feature of lariat formation, the intra-or extrahelical positioning of the bulged base has to be considered (34,42). The conformation of bulged nucleotides in RNA is not yet known, but by measuring ethidium bromide intercalation near bulged A, C, and U in an RNA helix, it was shown that all three bulged nucleotides have the same pronounced effect on the conformation of the sugar-phosphate backbone (60). Thus, the nucleotide conformations either are identical or differ by only a small free energy.…”
Section: Resultsmentioning
confidence: 99%
“…Bulged nucleotides have been shown to be important structural motifs in various RNAs (Wu and Uhlenbeck, 1987;White and Draper, 1987). In most cases, a C is present at residue 3 17 in severe to lethal PSTVd strains, whereas a U is present at this position in mild to intermediate strains (Schnolzer et a/., 1985;Zimmat et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 RRE <1 µM [176] 46 Delfinidin tRNA 10 µM [177] 47 Dichlorolissoclimide Inhibit eukaryotic protein synthesis 0.7 µM inhibition of protein synthesis only reported [166] 48 Doxycycline Small subunit fivefold tighter than tetracycline [167] 49 Erythromycin PTC 0.99 µM 1yi2 [178] 50 Ethidium bromide RNA/DNA heteroduplex, bulged RNA 3.3 µM [179,180] [189,190] 58 Hypoxanthine Guanine riboswitch 50 nM 2ees…”
Section: Db340mentioning
confidence: 99%